Water Resource Ecological Footprint and Suitable Carrying Population Size in Provincial Capitals of China - Luo Shuang; Zhang Xingqi; Xu Youpeng (Shuitu baochi tongbao, 2023)
[Objective] The water resource carrying capacity and appropriate population size of main provincial capitals in China were analyzed in order to provide a reference for implementing the policy of “determining population by water resources” and the strategy of urban sustainable development. [Methods] Based on water resources and population data, we used the ecological footprint method to analyze the ecological footprint of water resources and their water resource carrying capacity in the provincial capital cities of China from 2010 to 2020. The quota method was used with current domestic water consumption data to estimate the suitable carrying population scale for each provincial capital. [Results] ① More than half of the provincial capitals had less than 500 m3 of water per capita per year, and the domestic water consumption of most cities accounted for 20% of the total water consumption, while the domestic water use of Beijing City and Zhengzhou City accounted for 45% of the total water consumption. This high proportion of domestic water use put the urban water supply under great pressure. ② Cities with high per capita water resources have an ecological surplus of water resources. However, about two-thirds of the provincial capitals were in a state of ecological deficit. The highest per capita surplus from 2010 to 2020 was found for Nanning City (2.20 hm2/person). The greatest per capita deficit was found for Yinchuan City (-1.66 hm2/person). The distribution of ecological surplus and deficit of water resources showed a pattern of “surplus in the south, deficit in the north”, but some provincial capitals in the middle and lower reaches of the Yangtze River also showed deficits. ③ The suitable population in provincial capitals was evaluated based on the two water consumption scenarios of “extensive consumption” and “conservative consumption”. There was a large difference between the suitable population and the current population. [Conclusion] In order to promote sustainable economic and social development, cities with serious waste of water resources should strengthen the construction of water-saving cities, while cities with low domestic water standards should consider reducing their population in order to improve the water using experience and the quality of life of residents.